Analysis and evaluation of the effects of housing foundation activities on improving the physical and social dimension of development of rural settlements case study: Moghan County (Germi) Villages - Kalansara, Firouz Mahdizade; Jahani, Mahdi; Ahmadian, MohammadAli (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
Rural development has a close relationship with structural processes such as social and physical processes. Therefore, in this study, the effects of housing activities in two social and physical dimensions of villages in the city of Germi have been investigated.In order to know about the issues and the results of the preparation and implementation of these projects, it is necessary to study case studies of eligible villages, in this regard, to evaluate the plans of the rural municipality and villagers and the rural ownership document in the villages of Moghan (Germi) 55 villages of the city have been implemented. In this research, descriptive-analytic method has been used based on documentary studies and field operations (questionnaire, interview, etc.). Given the number of villages and the high number of households in rural areas, a sample size of 287 households was determined using the Cochran formula and distributed randomly among the households living in each village. The results of the research show that the relationship between the activities of the Housing Foundation and the social development of the villages is significant (the value is less than 0.05), the intensity of the relationship is 0.033, and the direct and the positive, as well as the relationship between the activities of the Foundation Housing and sustainable development of the villages are meaningful, (the value of which is less than 0.05), the intensity of the relationship is equal to 0.629, is direct and positive.